PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN SISWA-SISWI MEMILIH SEKOLAH DI MADRASAH ALIYAH NEGERI 1 BANJAR - Sri Hidayati Sri Hidayati (JURNAL KINDAI, 2022)
ABSTRACT This study aims to determine the effect of the marketing mix consisting of product, price, location/place, promotion, people, physical evidence, and process partially on students' decisions in choosing Madrasah Aliyah Negeri 1 Banjar and knowing the product, price, location/ place, promotion, people, physical evidence, and the joint process of students' decisions in choosing Madrasah Aliyah Negeri 1 Banjar. The research method used is multiple linear analysis method, using partial test and simultaneous test. The sample taken was 42 students of Madrasah Aliyah Negeri 1 Banjar for the academic year 2021/2022 using random sampling technique. The results showed that partially the variables known to be product, location/place, promotion, people, and process had a positive influence on students' decisions to choose schools at Madrasah Aliyah Negeri 1 Banjar, for other variables, namely price variables and physical evidence, there was no effect on the decision of students to choose a school at Madrasah Aliyah Negeri 1 Banjar. Meanwhile, the 7P variables together have a positive influence on students' decisions to choose schools at Madrasah Aliyah Negeri 1 Banjar. Keywords: Marketing Mix, Choice Decision, Madrasah Aliyah Negeri 1 Banjar